Associations between red meat intake and biomarkers of inflammation and glucose metabolism in women. Issue 2 (27th November 2013) - Ley, Sylvia H; Sun, Qi; Willett, Walter C; Eliassen, A Heather; Wu, Kana; Pan, An; Grodstein, Fran; Hu, Frank B
ABSTRACT: Background: Greater red meat intake is associated with an increased type 2 diabetes and cardiovascular disease risk. However, the relation of red meat intake to biomarkers of inflammation and glucose metabolism has not been investigated thoroughly. Objective: We hypothesized that greater red meat intake would be associated with biomarkers of inflammation and glucose metabolism, which would be partly explained by body mass index (BMI). Design: We analyzed cross-sectional data from diabetes-free female participants in the Nurses' Health Study ( n = 3690). Multiple linear regression was conducted to assess the associations of total, unprocessed, and processed red meat intakes (quartile categories) with plasma C-reactive protein (CRP), ferritin, adiponectin, fasting insulin, and hemoglobin A1c (Hb A1c ). Results: Greater total, unprocessed, and processed red meat intakes were associated with higher plasma CRP, ferritin, fasting insulin, and Hb A1c and lower adiponectin after adjustment for demographic information ( P -trend ≤ 0.03 for all). Adiponectin was not associated with any type of red meat intake when further adjusted for medical and lifestyle factors. After adjustment for BMI, most of these associations with inflammatory and glucose metabolic biomarkers were substantially attenuated and no longer significant. BMI accounted for a statistically significant proportion of associations with CRP, Hb A1c, and fasting insulin ( P -contribution ≤ 0.02 for all) but not with ferritin. Substituting a serving of total red meat intake with alternative protein food in a combination of poultry, fish, legumes, and nuts was associated with significantly lower CRP (β ± SE: −0.106 ± 0.043), ferritin (−0.212 ± 0.075), Hb A1c (−0.052 ± 0.015), and fasting insulin (−0.119 ± 0.036) (all P ≤ 0.02 for comparison of extreme quartiles for all). Conclusions: Greater red meat intake is associated with unfavorable plasma concentrations of inflammatory and glucose metabolic biomarkers in diabetes-free women. BMI accounts for a significant proportion of the associations with these biomarkers, except for ferritin. Substituting red meat with another protein food is associated with a healthier biomarker profile of inflammatory and glucose metabolism.